P120. MRI of the inner ear enables differentiation of central and peripheral vestibular pathologies in a postoperative ELST patient. Issue 8 (August 2018) - Kirsch, V.; Becker-Bense, S.; Berman, A.; Gerb, J.; Ertl-Wagner, B.; Dieterich, M.
Abstract : Introduction: An endolymphatic sac tumour (ELST) is a rare form of a locally invasive very slowly growing papillary epithelial neoplasm originating from the endolymphatic sac and/or duct (Wick et al., 2015 ). This single case study exemplifies the usefulness of delayed intravenous gadolinium-enhanced magnetic resonance imaging (iMRI) of the inner ear for differentiation of divers vestibular pathologies in complex cases of dizziness (Nakada et al., 2014 ). Case report & methods: A 48-year old, highly burdened right-handed female patient who had been operated on an ELST in the right petrosal bone presented with three different vestibular symptoms: (i) a persistent to-and-fro vertigo since 20 years, (ii) reproducible position-dependent short vertigo attacks accompanied by an inconsistent nystagmus when laying down on her side (R > L), and (iii) spontaneous rotational vertigo attacks for several hours associated by ear pressure, nausea, vomiting, and diarrhea. The diagnostic work-up included a careful neurootological and neuro-orthoptic assessment, videooculography during oculomotor examination (VOG), caloric stimulation (caloric) and head-impulse (HIT), audiometry, as well as an iMRI 4 h after injection of i.v. contrast agent (Nakada et al., 2014 ). Endolymphatic hydrops (ELH) was characterized by criteria previously described (Baráth et al., 2014 ). Volumetric assessment used manual segmentation in combination with machine learning and automated local thresholding algorithms (Gürkov et al., 2015 ). Results: The structural MRI showed a focal defect zone in the right cerebellar hemisphere. In line, the neuro-orthoptic examination revealed a cerebellar syndrome with downbeat-nystagmus (DBN) that increased when lying down on her R > L side. Furthermore, a right-sided audio-vestibular peripheral deficit was disclosed (HITmean gain: R = 0.66, L = 0.98; caloricsmean [°/s]: R = 4, L = 11; audiometrymean [dB]: R = 50, L = 15). The iMRI revealed a high-grade unilateral right-sided ELH (R = 87 mm3, Rcochlea (=c) = grade II-III, Rvestibule (=v) = grade III), whereas the left ear showed normal values (L = 32 mm3, Lc/v = grade 0). Discussion: On the basis of these results the (i) ongoing vertigo with (ii) exacerbation when lying down on the side could be assigned to a DBN syndrome with central positional vertigo due to the cerebellar lesion. The spontaneous attacks (iii) were caused by a secondary right-sided ELH. The differentiation of aetiologies allowed a stepwise treatment with a combination of 4-aminopyridine (5 × 5 mg/d) to improve the DBN and betahistin (3 × 48 mg/d) to improve the ELH. Both medications lead to a considerable clinical benefit. Here, iMRI was crucial in assigning a complex symptomatology to different central and peripheral vestibular pathologies resulting in a successful treatment (Brandt and Dieterich ).